SYNERGETIC APPLICATION OF ANSYS AND MATLAB FOR MODELING THE CONTACT INTERACTION OF A COMPLEX-SHAPED STAMP WITH AN ELASTIC HALF-SPACE - Zaytseva, T. A.; Honcharov, Ya. A. (Systems and Technologies, 2025)
An integrated methodology for numerical modeling of the contact interaction between a perfectly rigid punch of complex geometry and an isotropic elastic half-space is presented, based on the synergistic use of ANSYS and MATLAB. The approach treats the contact region as a doubly connected ring (annular domain) whose inner and outer boundaries are described by concen- tric curves, thereby capturing geometric features that strongly influence local stress fields. A finite-element model was constructed in ANSYS with due account of the intricate geometry, boundary conditions, and loading schemes; this enabled the computation of a detailed distribution of contact stresses and displacements under prescribed indentation scenarios. A systematic sensitivity analysis with respect to mesh density, local refinement near anticipated singular zones, and interpolation settings was performed, leading to practical convergence criteria and stable error tolerances suitable for repeated studies. Special attention was paid to adaptive discretization of the contact zone so as to ensure numerical convergence, suppress spurious oscillations, and improve the accuracy of peak-stress estimation along the edges of the active contact. Upon completion of the simulation, the computed fields were exported to MATLAB, where a dedicated post-processing pipeline was implemented to provide consistent graphical interpre- tation and quantitative comparison. In particular, masking outside the physically realized contact patch was applied to eliminate non-physical interpolation artifacts and to isolate the effective load-transfer area for analysis. The toolkit supports the generation of contour maps of contact pressure, 3D visualizations of the stress–strain state, and targeted diagnostics of edge effects, including the localization and ranking of stress concentration zones. The use of MATLAB also facilitates the identification of local features in the pressure distribution and regions of reduced contact interaction, and it enables structured parametric comparisons across multiple geometric variants and loading levels using a uniform set of metrics. Overall, the proposed methodology spans the full computational cycle–from geometric modeling and robust finite-element solution to standardized interpretation and reporting of results–and is designed to be scalable and amenable to scripting and automation for batch studies. The resulting datasets and visual products can be directly used for verification and validation of models, optimization of design parameters, and the development of applied engineering practices for contact mechanics problems, particularly in settings with complex interaction geometries and pronounced stress gradients where reliable resolution of edge behavior is essential.